The Electrical Performance of Epoxy Resin Insulator under Rain Contaminants - Abdul Syakur; Hermawan . (IAES Indonesia Section, 2014)
A polymeric insulating material as outdoor insulatorhas been developed and used on transmission lines and powerdistribution network. Each material has its own advantages anddisadvantages. Generally, polymeric materials have dielectricproperties better than the ceramic, glass and porcelain material.Factors affecting performance of outdoor insulators are like rain,humidity, ultraviolet rays, condensation and contaminant. When rainwater flow at the insulator surface, they will be easily contaminatedand flow current. These events can cause damage to the surface of theinsulator and finally cause flashover. To improve the surfaceproperties of materials, silicon rubber material that has the ability torepel water were added. Silica sand was mixed with silicon rubber toimprove the mechanical properties.This paper presents the electrical performance of epoxyresin insulator under rain contaminants. The tests were conducted athigh voltage laboratory with AC high voltage 50 Hz. Leakage currentcharacteristic of 20 kV outdoor insulators with silane epoxy resin hasbeen investigated under dry and wet condition. The chamber wasused to placing the insulator.The research results showed that the leakage currents oninsulator surface were affected rain contaminant and magnitude ofapplied voltage. A minimum leakage current achieved at outdoorinsulator without contaminant. For outdoor Insulator under raincontaminant, leakage current tends to increase. Shape of insulatorinfluence the leakage current also was analyzed.